Efficacy Of Fungicides, Plant Extracts And Bio-Agents Against Sclerotium Rolfsii Incitant Of Collar Rot Of Betelvine (Journal of Plant Disease Sciences, 2019)
Collar rot disease incited by Sclerotium rolfsii is major threat of betel vine cultivation in Vidarbha region of Maharashtra. Fungitoxic activities of different fungicides, plant extract and bio-agents was assayed against Sclerotium rolfsii and results revealed that mancozeb @ 0.2% and carboxin + thiram @ 0.1% exhibited cent percent inhibition. Among the plant extracts evaluated (each @10 %) in vitro, garlic extracts (32.14%) and ginger (32.45%) significantly superior over other tested plant extract. Amongst bio-agents Trichoderma harzianum, T. asperellum and T. atroviridie recorded 43.96, 37.01 and 23.80 per cent inhibition against Sclerotium rolfsii respectively. Least inhibition was noticed in Pseudomonas fluorescens i.e 3.74%.
Keywords: Sclerotium rolfsii; Betelvine wilt; Chemical plant extract; Bioagents